Maksimisasi Keuntungan Usaha Budidaya Rumput Laut Di Desa Lalombi Kecamatan Banawa Selatan Kabupaten Donggala - Yusup, Moh. Yusram; Laapo, Alimudin; Howara, Dafina (AGROTEKBIS, 2013)
Research on profit maximization farming seaweed to determine the maximum advantage of seaweed cultivation in Lalombi Village, Sub District of South Banawa, Donggala Regency, Determine the allocation the resources to maximize profits. Determination of the respondents selected the Systematic Random Sampling method. The method of sampling is that only the first element of a randomly selected sample, were subsequently selected elements systematically according to a pattern. Number of samples by taking 50% of the population of 60 farmers, in order to obtain a sample of 30 respondents who seek seaweed. The analysis used in this study is the analysis of Linear Programming. The analysis showed that the maximum benefit is obtained by of seaweed cultivation farmers in Lalombi village the amount of production as much as 21.173 kg /planting season which amounted to Rp 63.519.070/Planting Season. Resource allocation based on the cultivation of seaweed research is to increase the profits of 423,26 HOK Labor, as 33.876, 84 Kg and Seed Capital amounting to Rp 84.692.100.